Pengaruh Implementasi Sistem Manajemen Mutu ISO 9001:2015 Terhadap Kepuasan Peserta (Pelanggan) Dengan Mediasi Kualitas Layanan - Erna Nur Ma'sumah; Layaman Layaman (Esensi: Jurnal Bisnis dan Manajemen, 2019)
This study aims to analyze the effect of the Implementation of Quality Management Systems and Service Quality on the Satisfaction of Participants (Customers), as well as the Implementation of Quality Management Systems on Service Quality. Data collection through the distribution of questionnaires to participants of PT. Taspen. Regression analysis is used to prove the hypothesis. The results showed that the implementation of the Quality Management System and Service Quality affected the Participant Satisfaction and the Implementation of the Quality Management System affected the Service Quality. Implementation of the Quality Management System has a weak effect on Participant Satisfaction. This study also shows that the Implementation of Quality Management Systems to Participant Satisfaction is mediated by Service Quality. This result has several managerial implications.